Formulas and calculations for drilling, production, and workover - Lapeyrouse, Norton J. (Gulf Professional Pub., 2002)
Gives all the formulas and calculations likely to be needed in drilling operations. Newly updated material includes conversion tables into metric. Separate chapters deal with calculations for drilling fluids, pressure control, and engineering. Example calculations are provided throughout. Includes formulas for pressure gradient, specific gravity, pump output, annular velocity, buoyancy factor, volume and stroke, slug weight, drill string design, cementing, depth of washout, bulk density of cuttings, and stuck pipe.
Includes index.
Keywords: Oil wells -- Management -- Mathematics.; elektronické knihy; electronic books